siRNA-mediated inhibition of survivin gene enhances the anti-cancer effect of etoposide in U-937 acute myeloid leukemia cells - Jafarlou, M; Baradaran, B; Shanehbandi, D; Saedi, T A; Jafarlou, V; Ismail, P; Othman, F (Cellular and Molecular Biology, 2016)
Acute myeloid leukemia (AML) is one of the most frequent types of leukemia which mostly affects adult people. Resistance to therapeutic drugs is considered as a major clinical concern resulting in a weaker response to chemotherapy, disease relapse and decreased survival rate. Survivin, a member of Inhibitor of Apoptosis Proteins (IAPs), is associated with drug resistance and inhibition of apoptotic mechanisms in numerous hematological malignancies. In the present study, we examined the combined effect of etoposide and siRNA-mediated silencing of survivin on U-937 acute myeloid leukemia cells. The AML cells were transfected with survivin specific siRNA and gene knockdown was confirmed by quantitative real time PCR and western blotting. Subsequently, U-937 cells were assessed for response to etoposide treatment and apoptosis rate was measured with flowcytometery. The cytotoxic effects in siRNA-etoposide group were measured and compared to etoposide single therapy group. Survivin siRNA effectively knocked down the mRNA and protein levels of survivin, which led to lower cell proliferation and enhanced apoptosis. Furthermore, combined treatment of etoposide and survivin siRNA synergistically increased the cell toxic effects of etoposide and its ability to induce apoptosis.